The Influence of Entrepreneurship Education with in the Family and Business Capital on the Income of Handwoven Fabric Artisans in Sumber Harapan Village, Sambas District - Tisa, Tisa; Mashudi, Mashudi; Asriati, Nuraini (Pusdikra-Publishing.com, 2024)
This study aims to analyze: 1) The impact of entrepreneurial education in the family on the income of the manufacturer of fabrics in the village of Hope Branch of Sambas. 2) The effect of the capital of the enterprise on the revenue of the supplier of the fabrics of the village. The method used in this research is a method of quantitative research. The analysis technique in this study is double regression analysis. The sample in this study was a craftsman as well as a weaving business manager in the village of Hope Source of Sambas district with a total of 30 respondents. The data collection tool uses a lift or a questionnaire. The results of the study showed that: 1) Education of entrepreneurship in the family against the income of the craftsmen of the fabrics in the village of the source of hope of the district of Sambas has a significant influence. 2) Capital of the enterprise against the revenue of the manufacturers of fabrics of the village, while there are still 59.4% other determined of other factors not discussed in this study. Based on the results of the research, we expect fabric craftsmen to be able to improve entrepreneurial education in the family optimally and structured, the government and institutions are able to provide support in the form of additional capital of a larger enterprise so that the enterprise continues to go well and increases the income of fabric entrepreneurs.